Multiloop Control of Continuous Stirred Tank Reactor Using Biggest Log Modulus Method - Anbu, S. (Asian Journal of Electrical Sciences, 2016)
A majority of the chemical processes are naturally a Multi Input Multi Output (MIMO) system because of the existence of many loops where the interactions between the loops are high. In a Single Input Single Output (SISO) control, the primary objective is to maintain only one variable nearer to its set point, though several measured variables are involved. In contrast to SISO system, the MIMO control involves maintaining several controlled variables at their relevant setpoints simultaneously, Cha et al. (2002). For controlling MIMO systems, a single loop tuned controller design procedure cannot be directly applied because of the heavy interaction among the loops.. A Continuous Stirred Tank Reactor (CSTR) is one of the versatile reactors which find its application in many chemical and petrochemical industries, exhibiting reasonably high non-linear behaviour. The control of CSTR throws a challenge to the control engineers to design a well-suited controller for its smooth operation. The interaction in the CSTR is phenomenal and hence in this present work, the Biggest Log modulus Tuning (BLT) is designed for the CSTR and performances are evaluated under various operating conditions through simulation.